Hypoxia perturbs endothelium by re-organizing cellular actin architecture: Nitric oxide offers limited protection. (February 2018) - Swaminathan, Akila; Kasiviswanathan, Dharanibalan; Balaguru, Uma Maheswari; Kolluru, Gopi Krishna; SuryaKumar, Geetha; Chatterjee, Suvro
Highlights: Hypoxia induces alteration in actin filaments in chick embryo extra vascular model and endothelial cells. Hypoxia induces paracellular gaps in blood capillaries of chick embryo extra vascular model. NO confers protection against hypoxia-mediated cytoskeltal remodeling and endothelial leakiness. Abstract: Exposure to hypoxia causes structural changes in the endothelial cell (EC) monolayer that alter its permeability. There was a report earlier of impairment of nitric oxide (NO) production in endothelium. The intervention of NO in the altered cellular arrangements of actin cytoskeleton in endothelium for rectification of paracellular gaps in endothelium under hypoxia was observed. The present study demonstrates hypoxia inducing paracellular gaps in hypoxia-exposed blood capillaries in chick embryo extravascular model. Phalloidin staining confirmed significant polymerization of actin and unique cellular localization of the F-actin bands under hypoxia treatments. Addition of spermine NONOate (SPNO), a NO donor, or reoxygenation to endothelial monolayer attenuated hypoxia-mediated effects on endothelial permeability with partial recovery of endothelial integrity through actin remodeling. The present study indicates link of hypoxia-induced actin-associated cytoskeletal rearrangements and paracellular gaps in the endothelium with a low NO availability in the hypoxia milieu. The author concludes that NO confers protection against hypoxia-mediated cytoskeletal remodeling and endothelial leakiness.